2015
DOI: 10.1139/cjz-2015-0056
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Asian earthworms of the genus Amynthas alter microhabitat use by terrestrial salamanders

Abstract: Invasive earthworms are rapidly transforming detrital communities in North America. Recent studies have investigated the effects of European earthworms, whereas Asian earthworms, such as species of the genus Amynthas Kinberg, 1867, remain understudied. Amynthas is a surface-dwelling earthworm that voraciously consumes the litter layer of temperate forest floor habitats. The accumulation of detritus is important for the terrestrial Eastern Red-backed Salamanders (Plethodon cinereus (Green, 1818)) because this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…As warmer, drier conditions continue to facilitate earthworm invasions, we would expect these factors to exert strong negative effects on terrestrial dwelling, lungless salamanders (Brunges et al, 2020). Evidence suggests that nonnative earthworms consume leaf litter microhabitat that houses salamander fDprey at very rapid rates and that these invaders are negatively associated with juvenile and male red-backed salamanders in the field (Ziemba et al, 2015(Ziemba et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…As warmer, drier conditions continue to facilitate earthworm invasions, we would expect these factors to exert strong negative effects on terrestrial dwelling, lungless salamanders (Brunges et al, 2020). Evidence suggests that nonnative earthworms consume leaf litter microhabitat that houses salamander fDprey at very rapid rates and that these invaders are negatively associated with juvenile and male red-backed salamanders in the field (Ziemba et al, 2015(Ziemba et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a previous laboratory microcosm experiment that found altered P . cinereus microhabitat use in the presence of pheretimoid earthworms and increased importance of CO microhabitat following earthworm-mediated LL consumption [ 41 ]. In the present study, salamanders used low quality microhabitat (dry areas outside of the CO) significantly more often when paired with earthworms than when alone in laboratory trials.…”
Section: Discussionmentioning
confidence: 99%
“…The only study that has examined the effect of large pheretimoid earthworms on P . cinereus behavior found altered salamander CO use and increased salamander movement between microhabitats over time as LL was consumed by earthworms in laboratory microcosms [ 41 ]. Since large pheretimoid earthworms remove the detrital habitat of salamanders, but do not construct permanent soil burrows that serve as an alternate spatial resource, impacts of their invasion on P .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, two studies in Ohio found that non-native Amynthas earthworms alter microhabitats and behavior of P. cinereus. The first found that earthworm presence decreased leaf litter mass over time, leading salamanders to increase movement, cover object use, and co-occurrence under cover objects with earthworms (Ziemba et al, 2015). A follow-up study found further evidence the salamanders were negatively impacted by Amynthas and Metaphire spp.…”
Section: (H) Community Ecologymentioning
confidence: 98%